Internalization, international diversification and the multinational enterprise essays in honor of Alan M. Rugman - Verbeke, Alain (Emerald, 2005)
This research volume includes a synthesis of recent advances in the theory of the multinational enterprise, with a focus on internalization and international diversification issues. It proposes important extensions of multinational enterprise theory, especially as regards the importance of geography to multinational strategy, and the linkages between internalization and international diversification. The book also introduces the study of various new topics in international business research, namely regional (as opposed to global) strategy analysis, global alliances that lead to alliance specific advantages, and environmental aspects of international strategy. The ten chapters that provide this state of the art overview of international business theory and strategy were written by some of the world's best known international business scholars, including John Cantwell, John Dunning, Lorraine Eden, Jean Francois-Hennart, Ans Kolk, Alan M. Rugman, Alain Verbeke and Bernard Wolf. The research volume focuses especially on the important contributions of Alan M. Rugman, President of the Academy of International Business, and one of the founders of the international business field. The volume's editor is Professor Alain Verbeke, McCaig Chair in Management at the Haskayne School of Business, University of Calgary (Canada) and also associated with Templeton College, University of Oxford (UK), and the Solvay Business School, Free University of Brussels (Belgium).
Includes index.
Keywords: Business & Economics -- International -- Economics.; Business & Economics -- Finance.; Multinationals.; International business enterprises.; elektronické knihy; electronic books